(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The concept of Microfinance has introduced in Bangladesh by Mahammad Yunuas. He has the aim to establish equity and social justice. He has strongly faith public awareness, financial accessibility and sustainable development is possible only through the microfinance. According to him Microfinance should be reach the tail end person in rural areas. It helps to strengthen the rural economy it leads to rural development. Microfinance Itself indicates small scheme financial requirements of the poor people in rural areas. It provides loans, savings accounts, and other financial products to low-income individuals and groups. Self sufficiency of the people is the primary objective of the micro finance in India is financial institutions that make small loans to persons who do not have access to traditional banking services. The term “small loans” is defined differently in different nations. In India, it is defined as loans of less than one lakh rupees are called micro credit. Micro finance institutions have increased in India as well as Karnataka in recent days.